Comparative Study of Adsorption Ability of Ni(II) and Zn(II) Ionic Imprinted Amino-Silica Hybrid Toward Target Metal in Solution - Buhani; Suharso; Yuli Fitriyani, Andi (Asian Journal of Chemistry, 2012)
This research investigated comparative study of adsorption ability from Ni(II) and Zn(II) ionic imprinted polymer [Ni(II)-IIP and Zn(II)-IIP] amino-silica hybrid to each Ni(II) and Zn(II) ion as a target metal. Adsorbent synthesis was carried out via sol-gel process with an active compound 3-aminopropyltrimethoxysilane and a silica matrix from tetraethylorthosilicate. Series of experiments with batch method were performed to determine adsorption kinetics, isotherm and selectivity of adsorbent Ni(II)-IIP toward Ni(II) target ion and Zn(II)-IIP toward Zn(II) target ion in solutions. Kinetic models of Ni(II) and Zn(II) ion for all adsorbents tend to follow a pseudo second order kinetic model and a Dubinin-Raduskevich (D-R) isotherm adsorption model. The adsorption capacity value (qDR) of Ni(II) ion on non-imprinted polymer (NIP) and Ni(II)-IIP is each 21.674 and 31.478 mg g-1, while the adsorption capacity value of Zn(II) ion on Zn(II)-NIP and Zn(II)-IIP is 19.255 and 24.633 mg g-1. The selectivity coefficient (a) value for each adsorbent shows that Ni(II)-IIP adsorbent is more effective upon its Ni(II) ion target metal than Zn(II)-IIP adsorbent with Zn(II) ion as its target.